STUDYING THE NEED TO INTEGRATE STEM APPROACHES TO IMPROVING COMPUTER SCIENCE TEACHING IN KAZAKHSTAN, CHINA, AND JAPAN - Uksikbayev Е.З.; Bostanov Б.Г.; Amanov А.Н. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2025)
The integration of STEM (Science, Technology, Engineering, Mathematics) approaches in the modern education system is an important tool for improving knowledge and skills in the field of Information Technology. This study analyzes the need to implement STEM approaches, comparing the experience of teaching computer science in secondary schools in Kazakhstan, China and Japan. The purpose of the study is to identify the specifics of teaching computer science in the educational systems of the three countries, evaluate the effectiveness of STEM methods and propose optimal ways to integrate them into the learning process. In the course of the study, qualitative and quantitative methods are used, regulatory documents, training programs, experience of teachers and students are analyzed. The results will prove the importance of introducing STEM approaches to improve the teaching of computer science in Kazakhstan, as well as adapt the best practices of China and Japan. This study shows that by integrating STEM areas into school computer science, they contribute to improving algorithmic thinking, creativity, and technical literacy of students.